Keberlanjutan Fikih Lingkungan: Studi Program Pelestarian Lingkungan Hidup di Pesantren Tebuireng - Ramadhan, M. Rizki Syahrul; Faozan, Ahmad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Ideas about environmental jurisprudence from Islamic boarding school intellectuals tended to experience stagnation after the KH era. Sahal Mahfudz and KH. Ali Yafie. However, the development of these ideas in the form of programs continues in many Islamic boarding schools. This article examines these developments at the Tebuireng Islamic Boarding School. The Tebuireng Islamic Boarding School was chosen because in recent years it has succeeded in making rapid developments in the field of waste management and has been recognized by the Ministry of the Environment as a model Islamic boarding school. To reveal the environmental preservation program at the Tebuireng Islamic Boarding School and its position as a continuation of environmental jurisprudence studies, this field research chose a qualitative type with an anthropological approach. In-depth interviews and participant observation were carried out to maximize data mining. As a result, it is known that environmental conservation efforts at the Tebuireng Islamic Boarding School, which began with a waste management program, are a series of long-term programs towards comprehensive environmental preservation including land, water and air. All parts of this long-term program were carried out with awareness of the need to actualize the ideas of environmental jurisprudence that had been initiated by Islamic boarding school intellectuals and their example.